(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Self-esteem can be measured by several explicit measurement tests, but it has also been evaluated through implicit measurement tests. The Function Acquisition Speed Test (FAST) has been used in the literature to access implicit measures like gender stereotypes. The objectives of this study were to verify if the FAST is sensitive to relationships that are part of the concept of self-esteem and to compare its results with the Rosenberg Self-Esteem Scale (RSE). A remote application of a version of the FAST was conducted with 50 university students, along with the RSE. The results showed that the students displayed positive self-esteem both in the FAST and the RSE, but there was no statistical correlation between the results of these measures. The findings suggest that the FAST can be used to study self-esteem and that it measures a different type of self-esteem compared to the RSE.